2021
DOI: 10.1109/jphotov.2021.3057169
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Photovoltaic Systems Using Improved Kernel-Based Learning Schemes

Abstract: Data-based procedures for monitoring the operating performance of a PV system are proposed in this paper. The only information required to apply the procedures is the availability of system measurements, which are routinely on-line collected via sensors. Here, kernel-based machine learning methods, including support vector regression (SVR) and Gaussian process regression (GPR), are used to model multivariate data from the PV system for fault detection due to their flexibility and capability to nonlinear approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 51 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Moreover, SVR models proved to be efficient in the presence of limited samples 66 . Additionally, SVR has been broadly applied in various applications, including wind power forecasting 67 , fault detection 8 , and solar irradiance prediction 48 . This study built six SVR models using different kernels and an optimized SVR using Bayesian optimization (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, SVR models proved to be efficient in the presence of limited samples 66 . Additionally, SVR has been broadly applied in various applications, including wind power forecasting 67 , fault detection 8 , and solar irradiance prediction 48 . This study built six SVR models using different kernels and an optimized SVR using Bayesian optimization (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…During this pandemic, AI showed to be useful in predicting outbreaks and aid assemble quickly evolving data to support general health specialists in complex decision-making 7 . In addition, various AI-based tools were designed in the healthcare field 3 , 6 , 8 . For instance, a team at Boston Children’s Hospital developed an automated electronic information system called Health Map 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different classifiers were used to evaluate the learning model, and results indicated that RF has the capability to provide the best results. Harrou et al [69] elaborated ML prediction frameworks including SVM, Gaussian Process Regression (GPR), and mapping-based kernel machines for condition monitoring of PV systems. Six fault types specified by bridging faults and partial shading, and PV module short circuits, module degradation, and line-to-line faults, were examined using P-V analysis.…”
Section: Ml-based Ordinary Sensorsmentioning
confidence: 99%
“…Specifically, this study investigates the forecasting ability of the optimized GPR, a kernel-based machine learning method, in forecasting the COVID-19 time series. This choice is motivated by the desirables features of the GPR model, including its simple and flexible construction using the mean and covariance functions, its ability and superior nonlinear approximation, and the possibility to explicitly provide a probabilistic representation of forecasting outputs [13], [14]. Specifically, the BO algorithm is employed to find the optimal hyperparameters of the GPR model to improve the forecasting quality.…”
Section: Introductionmentioning
confidence: 99%